Digital Animation Media to Improve Learning Motivation in Elementary Science Education - Nurul Maghfira; Muhammad Aqil; Surahman Wilade; Nasrullah Nasrullah; Ryan Andhika Pratama; Pahriadi Pahriadi (CV. Dharma Samakta Edukhatulistiwa, 2026)
This study aims to examine the effectiveness of educational animated videos as a medium for science learning. In addition, this study aims to investigate the differences in students’ learning enthusiasm between students taught using animated videos and those taught using conventional teaching methods. This study employed a Research and Development (R&D) approach using the ADDIE development model involving fifth-grade students at SD Negeri 22 Palu. Data were collected through observations, interviews, validation questionnaires, and learning motivation questionnaires, then analyzed using descriptive quantitative and qualitative techniques. The media obtained a validity score of 89.82% and a practicality score of 86.46%, categorized as very valid and practical. The media also helped teachers deliver learning materials more clearly, interactively, and effectively for students. In addition, the use of animated videos can increase student participation and engagement during the learning process. Furthermore, the developed media demonstrated high practicality and effectiveness in supporting elementary students’ science learning.